2007
DOI: 10.1007/s11627-007-9030-0
|View full text |Cite
|
Sign up to set email alerts
|

Plant regeneration of common ash (Fraxinus excelsior L.) by somatic embryogenesis

Abstract: This is the first report on somatic embryogenesis in common ash (Fraxinus excelsior L.). Experiments on somatic embryogenesis induction were carried out on zygotic embryos at different phases of development and maturation. The embryo axes were isolated and cultured on media containing different plant growth regulators (PGRs). Embryogenic tissues were obtained from embryos collected at an incomplete maturation phase and cultured on a modified Murashige and Skoog medium containing 8.8 μM 2,4-dichlorophenoxyaceti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 29 publications
2
10
0
Order By: Relevance
“…Choi et al [15] assumed that higher concentrations of 2,4-D might result in a greater possibility of somatic mutation. The use of cytokinins in combination with auxins has been reported to promote callus induction [16]. Similarly, we observed that the addition of 0. )…”
Section: −1supporting
confidence: 79%
“…Choi et al [15] assumed that higher concentrations of 2,4-D might result in a greater possibility of somatic mutation. The use of cytokinins in combination with auxins has been reported to promote callus induction [16]. Similarly, we observed that the addition of 0. )…”
Section: −1supporting
confidence: 79%
“…These results were in accordance with Sharma et al, 2011(Sharma et al, 2011. The callus induction was also promoted by the combination of cytokinin and auxins (Capuana et al, 2007). TDZ is also considered to be one of the most active cytokinins for the shoot induction in plant tissue culture (Pelah et al, 2002;Mithila et al, 2003).…”
Section: Discussionsupporting
confidence: 73%
“…Somatic embryogenesis is generally promoted by auxins, either alone or in combination with cytokinins (Fei et al 2002;Shahana & Gupta 2002;Anthony et al 2004;Shu et al 2005). The use of cytokinins in combination with auxins has been reported to promote somatic embryogenesis induction (Liu et al 2008;Capuana et al 2007). …”
Section: Resultsmentioning
confidence: 99%